The Theory of Economic Growth / An Introduction - Hacche Graham; Macmillan Company (1979)
This textbook provides an introductory but comprehensive account of the modern theory of economic growth for intermediate-level and graduate students. Preface and Acknowledgements, Introduction, The Emergence of Modern Growth Theory - The Harrod-Domar Models, The Development of Modern Growth History - A Preview, Neo-Classical Growth Theory, Fixed Versus Variable Coefficients - The Neo-Classical Approach, The One-Good Model without Technical Progress - The Simplest Case, The Two-Sector Model without Technical Progress, Technical Progress and Productivity Growth and Steady States, Technical Progress - Theories of Bias and Neutrality, Technical Progress at an Endogenous Rate, Neo-Keynesian Growth History, Neo-Keynesian Criticisms of Neo-Classical Theory, Income Distribution and Effective Demand, Full Employment and Saving and the Flexibility of Profit Margins, Investment and Growth - Kaldor's Growth Model, Steady Growth and Economic History, Stylized Facts and Steady Growth and Structural Change, Stylized Facts and Historical Statistics, Notes and References, Bibliography, Index.